Enzymatic photosynthesis of formate from carbon dioxide coupled with highly efficient photoelectrochemical regeneration of nicotinamide cofactors. Issue 22 (12th October 2016) - Nam, Dong Heon; Kuk, Su Keun; Choe, Hyunjun; Lee, Sumi; Ko, Jong Wan; Son, Eun Jin; Choi, Eun-Gyu; Kim, Yong Hwan; Park, Chan Beum
Abstract : We present the photoelectrochemical (PEC) regeneration of nicotinamide cofactors (NADH) coupled with the enzymatic synthesis of formate from CO2 towards mimicking natural photosynthesis. Abstract : We present the photoelectrochemical (PEC) regeneration of nicotinamide cofactors (NADH) coupled with the enzymatic synthesis of formate from CO2 towards mimicking natural photosynthesis. The water oxidation-driven PEC platform exhibited high yield and the rate of NADH regeneration was compared to many other homogeneous, photochemical systems. We successfully coupled solar-assisted NADH reduction with enzymatic CO2 reduction to formate under continuous CO2 injection.